Tren topik dan indeksasi artikel arsip pada Science and Technology Index (SINTA) - Restu, Rifiani Aulia; Sudiar, Nining; Amalia, Vita (Daluang: Journal of Library and Information Science, 2025)
Purpose. This study aims to determine the topic trends and indexation of archival articles on the Science and Technology Index (SINTA) from 2020 to 2024. Methodology. The research method used in this study is quantitative descriptive with search on the SINTA platform and data analysis using web voyant tools. Results and discussion. The results of the study show that in the last five years, there have been 290 archive articles with a total of 1,420 keywords. The trend of topics seen by keywords is dominated by the keywords "archive," "record," and "digital." However, every year there is an expansion of research themes such as legal aspects, content specialization, and governance that strengthen archival as a field that is able to respond to the challenges of the times without losing its original identity. Meanwhile, indexation of archival journals tends to have low indexation with a high category (70%) dominated by Garuda indexation, and for medium indexation it is in the low category or with a percentage of 25% while high indexation is categorized as very low, which is 5%. Conclusions. Overall, the study shows that while interest in archival research still needs to be increased, there are great opportunities for future development, especially by leveraging digital technologies and expanding academic networks. Systematic efforts from various stakeholders can help improve the quality and impact of archival research at the national and international levels.